2012
DOI: 10.1021/jp301817e
|View full text |Cite
|
Sign up to set email alerts
|

Water Is a Poor Solvent for Densely Grafted Poly(ethylene oxide) Chains: A Conclusion Drawn from a Self-Consistent Field Theory-Based Analysis of Neutron Reflectivity and Surface Pressure–Area Isotherm Data

Abstract: By use of a combined experimental and theoretical approach, a model poly(ethylene oxide) (PEO) brush system, prepared by spreading a poly(ethylene oxide)-poly(n-butyl acrylate) (PEO-PnBA) amphiphilic diblock copolymer onto an air-water interface, was investigated. The polymer segment density profiles of the PEO brush in the direction normal to the air-water interface under various grafting density conditions were determined by using the neutron reflectivity (NR) measurement technique. To achieve a theoreticall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 40 publications
5
28
0
Order By: Relevance
“…The high resistance to elution at low peptide surface density is consistent with our earlier report and attributed to association of the amphiphilic WLBU2 with PEO chain segments in the hydrophobic inner region of the brush [1, 21, 24]. The elutability of S-WLBU2 and PLR was less strongly affected by the peptide surface density, and both were more elutable than WLBU2 at all but the highest surface density tested.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…The high resistance to elution at low peptide surface density is consistent with our earlier report and attributed to association of the amphiphilic WLBU2 with PEO chain segments in the hydrophobic inner region of the brush [1, 21, 24]. The elutability of S-WLBU2 and PLR was less strongly affected by the peptide surface density, and both were more elutable than WLBU2 at all but the highest surface density tested.…”
Section: Resultssupporting
confidence: 90%
“…In the presence of F108-coated nanoparticles at 1, 2, 4 and 10 mg/mL (corresponding to decreasing peptide surface densities of 0.20, 0.18, 0.14 and 0.02 molecules/nm 2 ), the helicity of WLBU2 was increased to 50, 65, 84 and 95%, respectively. The increase in helicity is due to promotion of hydrogen-bonding along the peptide backbone, which accompanies the change in microenvironment caused by location within the hydrophobic interior of the PEO layer [1, 5, 24]. Interference with this intra-chain hydrogen-bonding by neighboring peptides is presumably responsible for the reduction in α -helix content observed at increased peptide surface densities (Figure 4, left panel).…”
Section: Resultsmentioning
confidence: 99%
“…As discussed in detail in our previous publication, 56 the sharp plateau transition in the isotherm of the PnBA homopolymer (black curve) at an area per PnBA monomer of α o ≈ 21.6 Å 2 is due to the formation of a flat (i.e., laterally uniform) single-monomer-thick continuous film of PnBA that is free of voids at that polymer surface concentration. Our previous studies have also demonstrated that, thanks to this property of PnBA, at areas per PnBA monomer less than α o , the monolayer domain formed at the air-water interface by PnBA can be used as end-grafting sites for PEO or PDMAEMA chains for preparation of model non-adsorbing PEO 58, 66 or PDMAEMA 57, 62 brush systems. As shown in Figure 1(A), the monolayers of the block copolymers also exhibit a similar transition in their isotherm curves, all at an essentially identical value of area per PnBA monomer (α o = 21.4 ± 0.5 Å 2 ), which indicates that this transition behavior of PnBA is unaffected, regardless of whether the PnBA segment is present as an isolated chain or in the form of a component block of a diblock or a triblock copolymer.…”
Section: Resultsmentioning
confidence: 97%
“…Specifically, a laterally-mobile mixed PEO and PDMAEMA brush was prepared by spreading a mixture of two diblock copolymers, poly(ethylene oxide)-poly( n -butyl acrylate) (PEO-PnBA) and poly(2-(dimethylamino)ethyl methacrylate)-poly( n -butyl acrylate) (PDMAEMA-PnBA), onto the air-water interface. Here, PnBA was used as the common hydrophobic block for these copolymers, because the PnBA polymer forms a flat, single monomer-thick, continuous film (free of bare areas) at the air-water interface, 56 and also the grafted PEO and PDMAEMA chains do not have any tendency to adsorb to the surface of the anchoring domain formed by PnBA, 57, 58 which makes the PEO-PnBA and PDMAEMA-PnBA block copolymers uniquely suited for preparation of model non-adsorbing PEO/PDMAEMA brush systems. A laterally-mobile mixed PEO and PDMAEMA brush was prepared from a mixture of PEO 113 -PnBA 100 and PDMAEMA 118 -PnBA 100 diblock copolymers, where the subscripts refer to the number-average degrees of polymerization of the individual blocks; note that, as will be analyzed, in this case the heights of the PEO and PDMAEMA brushes are estimated to be (slightly) mismatched (that is, they differ by a factor less than about two).…”
Section: Introductionmentioning
confidence: 99%
“…The brush layers produced by adsorption of triblock surfactants on hydrophobic silica nanoparticles exhibit substantial repulsion of large proteins, as well as theoretical and experimental evidence of a non-polar microenvironment [3] at the triblock-coated surface (see Supporting Information). Our previous results indicated that the adsorption of small peptides of similar size at the pendant PEO layer is governed by their secondary structure, with the extent of entrapment and elution being determined primarily by the peptide amphiphilicity and surface density.…”
Section: Introductionmentioning
confidence: 99%